The Development of IoT Automatic Solar Tracking System for Oriented Solar Cell Applications - Hamidin, Muhamad Faris; Sadun, Amirul Syafiq (Progress in Engineering Application and Technology, 2023)
Creating a solar tracking system that will allow solar panels to constantly be pointed in the direction of the strongest radiation is the aim of this project. The quantity of sunlight absorbed in the morning, noon, and afternoon are not equal since the amount fluctuates during the course of a day. In Malaysia, there is also a significant amount of cloud cover, which causes the amount of solar output to vary greatly. The project’s primary purpose is to develop a solar tracking system that can detect the light intensity, auto movement of the solar tracking system, monitor the output from solar panel, and discuss the output data. During operation, a solar tracking system is controlled using the ESP32 because it is ideal for achieving IoT. ESP32, as a microcontroller will connect to KY-018 photoresistor module, also known as light dependent resistor. This photoresistor function is to detect the light intensity and auto directed the tracking system the point, where is light outmost. 2 servo motors will act to control the horizontal and vertical axis from the output from the photoresistor. The mechanical design and output from the solar are the type of testing that will be done. Therefore, based on the output values, the movement tests have shown that this system can work properly.